Development and validation of Japanese version of alternative food neophobia scale (J-FNS-A): association with willingness to eat alternative protein foods - Kamei, Mio; Nishibe, Misaki; Horie, Fuyumi; Kusakabe, Yuko (Frontiers in Nutrition, 2024)
Introduction: Food neophobia (FN) is a psychological trait that inhibits one's willingness to eat unfamiliar foods. It is related to the acceptance of insect foods and cultured meat, which are major protein alternatives to conventional meat, and is an important personality trait for understanding the near-future food industry. However, the factor structure of Pliner and Hobden's FN scale (FNS) is unstable due to respondents' cultural backgrounds. Thus, we aimed to develop a Japanese version based on the alternative FNS (FNS-A), the most recent revised version, and to examine its validity.